The Relationships between Addiction to Highly Caffeinated Drinks, Burnout, and Attention-Deficit/Hyperactivity Disorder - Bae, Eun Ju; Kim, Eun Bi; Choi, Bo Ram; Won, Sun Ho; Kim, Ji Hwan; Kim, Sun Min; Yoo, Hyun Jeong; Bae, Sung Man; Lim, Myung Ho (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2019)
This study aimed to evaluate the addiction to highly caffeinated drinks among university students, and we investigated the relationships between smartphone addiction, depression, anxiety, attention-deficit/hyperactivity disorder (ADHD), burnout, self-esteem, impulsiveness in high caffeine drink addiction risk group (high caffeine group). We also compared these mental health factors differences between the high caffeine group and the control group; and, investigated the relative risk between the independent variables of the high caffeine group. This study was conducted in Korea, from June 2015 to July 2016. A set of questionnaires was administered on 511 college students. The participants who belonged to the high caffeine group were more likely to demonstrate the symptoms of ADHD and higher levels of burnout and impulsiveness. Further, the results of logistic regression analysis confirmed the association between the high caffeine group and burnout. These behaviors among university students addicted to highly caffeinated drinks suggests the need for timely and effective interventions for those at risk of addiction.